The Roles of General Election Commission and General Election Supervisory Board for a Democratic Election - Marzuki, Suparman (Jurnal Hukum IUS QUIA IUSTUM, 2009)
To build a strong and reliable democratic institution, is a time consuming process which also requires a long patience. Accordingly, three pillars of General Election Commission (KPU), namely, structural independency, functional independency and personal independency, shall be consistently kept up and maintained. Keywords: General Election Commission, General Election Supervisory Board, Democratic